Export and Economic Growth in the Case of the Manufacturing Industry: Panel Data Analysis of Developing Countries - Kılavuz, Emine; Topcu, Betül Altay (International Journal of Economics and Financial Issues, 2012)
The correlation between growth in export and economic growth, which is called “Export-led Growth Hypothesis” in the literature, is still a current issue in both the theoretical and empirical literature. In the present study, the effect of different classifications of export and import on economic growth in 22 developing countries in the 1998–2006 period was tested based on two models, via panel data analysis. According to the results of the first model, the analysis of which included variables such as high and low-tech manufacturing industry exports, investment and population, it was found that only two variables, high-tech manufacturing industry export and investment, have a positive and significant effect on growth. In addition to the first model which included the analysis of all variables, the second model investigated the effect of high and low-tech manufacturing industry imports on growth. The findings revealed that only high-tech manufacturing industry export, investment and low-tech manufacturing industry import have a positive and significant effect on growth. Keywords: High and Low-tech Manufacturing Industry Imports and Exports; Economic Growth; Export-led Growth Hypothesis; Developing Countries; Panel Data Analysis JEL Classifications: F14; F43